2022
DOI: 10.1002/vzj2.20189
|View full text |Cite
|
Sign up to set email alerts
|

Examining subsurface response to an extreme precipitation event using HYDRUS‐1D

Abstract: North-central Colorado experienced an extreme precipitation event (EPE) in September 2013, during which the equivalent of 80% of the region's annual average precipitation fell in a few days. Widespread flooding occurred above ground, but the shortand long-term subsurface response remains unclear. The objective of the study is to better understand the dynamic subsurface response, namely how the water table and soil water storage responded to a large amount of infiltration in a short period of time and how the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Mechanistically, recharge is primarily controlled by the antecedent water content, thickness, and infiltration capacity of the vadose zone (de Vries & Simmers, 2002;Fetter & Kreamer, 2021). The vadose zone effectively acts as a reservoir that can store extreme event water (Corona & Ge, 2022), functioning as a recharge signal filter. In many cases, extreme precipitation is an important contributor to groundwater recharge (Corona et al, 2023;Thomas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, recharge is primarily controlled by the antecedent water content, thickness, and infiltration capacity of the vadose zone (de Vries & Simmers, 2002;Fetter & Kreamer, 2021). The vadose zone effectively acts as a reservoir that can store extreme event water (Corona & Ge, 2022), functioning as a recharge signal filter. In many cases, extreme precipitation is an important contributor to groundwater recharge (Corona et al, 2023;Thomas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Herrada et al (2014) proposed a model to predict infiltration rates. Corona and Ge (2022) were focusing on high intensity precipitation events. Tran et al (2016) showed that taking heat transport into account yields better results for an inversion scheme to define soil parameters.…”
Section: Introductionmentioning
confidence: 99%
“…(2014) proposed a model to predict infiltration rates. Corona and Ge (2022) were focusing on high intensity precipitation events. Tran et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is often used for the estimation of SHPs and solute transport properties, SWC, water infiltration, soil evaporation, root uptake, and groundwater recharge (e.g. Gogolev 2002, Bethune et al 2008, Jiménez-Martínez et al 2009, Mattern and Vanclooster 2010, Stumpp et al 2012, Sutanto et al 2012, Corona and Ge 2022, Liebhard et al 2022, Stafford et al 2022.…”
Section: Introductionmentioning
confidence: 99%